Practitioner’s guidebook and toolkit for agricultural policy reform: The P.M.C.A. approach to strategic policy engagement - Sitko, Nicholas J.; Babu, Suresh Chandra; Hoffman, Barak (Michigan State University, 2017)
This guidebook, and associated tools, is designed to help agricultural policy practitioners improve the effectiveness of their engagement with policy systems in developing countries. It provides practitioners with conceptual tools and practical strategies designed to improve the quality of policy practitioners’ efforts to influence complex agricultural policy systems. It develops a strategic approach to policy engagement termed the P.M.C.A. approach, and provides concrete applications and examples of this approach to help users apply the approach to their own policy domains of interest.